Plasma chemistry of SOx in a pulsed electric discharge at atmosphere pressure - Berezina, G.P.; Onishchenko, I.N.; Us, V.S. (Вопросы атомной науки и техники, 2000)
The theoretical and experimental investigations of gases SO₂ and SO₃ dissociation by using the pulsed spark discharge at atmosphere pressure are represented. The production of SOx (SO₂, SO₃ ) was performed in a special device by means of electric arc discharge at the sulphur burning in gases mixture of 80% O₂ and 20% Ar. The efficient decay of SOx radicals in the pulsed spark discharge jumping between a plate and a set of eagles has been demonstrated. It has been shown that the multispark discharge decomposes SOx radicals by more than 20% during tens minutes with a simultaneous release of decomposition products from the gas phase of substance.